PENERAPAN METODEPEMBELAJARAN SIMULASI UNTUK MENINGKATKAN PERCAYA DIRI DAN PRESTASI BELAJAR - Ahmad Daili (DIADIK, 2022)
The purpose of this study was to increase self-confidence and learning achievement in social studies at SD N 1 East Merapi, Lahat, class VI. The method used is CAR, with three cycles, followed by quasi-experimental. The research subjects for CAR were class VI.c, while the experimental class VI.a and control class VI.b. Data collection techniques using observation and tests. Data analysis used percentage, average and t test. Based on the data analysis, it can be concluded that the application of the simulation method can significantly increase self-confidence and social studies learning achievement